NLRX1 negatively modulates type I IFN to facilitate KSHV reactivation from latency. - Zhe Ma (PLoS Pathogens, 2017)
Kaposi's sarcoma-associated herpesvirus (KSHV) is a herpesvirus that is linked to Kaposi's sarcoma (KS), primary effusion lymphoma (PEL) and multicentric Castleman's disease (MCD). KSHV establishes persistent latent infection in the human host. KSHV undergoes periods of spontaneous reactivation where it can enter the lytic replication phase of its lifecycle. During KSHV reactivation, host innate immune responses are activated to restrict viral replication. Here, we report that NLRX1, a negative regulator of the type I interferon response, is important for optimal KSHV reactivation from latency. Depletion of NLRX1 in either iSLK.219 or BCBL-1 cells significantly suppressed global viral transcription levels compared to the control group. Concomitantly, fewer viral particles were present in either cells or supernatant from NLRX1 depleted cells. Further analysis revealed that upon NLRX1 depletion, higher IFNβ transcription levels were observed, which was also associated with a transcriptional upregulation of JAK/STAT pathway related genes in both cell lines. To investigate whether IFNβ contributes to NLRX1's role in KSHV reactivation, we treated control and NLRX1 depleted cells with a TBK1 inhibitor (BX795) or TBK1 siRNA to block IFNβ production. Upon BX795 or TBK1 siRNA treatment, NLRX1 depletion exhibited less inhibitory effects on reactivation and infectious virion production, suggesting that NLRX1 facilitates KSHV lytic replication by negatively regulating IFNβ responses. Our data suggests that NLRX1 plays a positive role in KSHV lytic replication by suppressing the IFNβ response during the process of KSHV reactivation, which might serve as a potential target for restricting KSHV replication and transmission.